2016
DOI: 10.1007/s11999-015-4631-0
|View full text |Cite
|
Sign up to set email alerts
|

A Radiation Safety Training Program Results in Reduced Radiation Exposure for Orthopaedic Residents Using the Mini C-arm

Abstract: Background Fluoroscopy during fracture reduction allows a physician to assess fractures and immediately treat a pediatric patient. However, concern regarding the effects of radiation exposure has led us to find ways to keep radiation exposures as low as reasonably achievable. One potentially simple way, which to our knowledge has not been explored, to decrease radiation exposure is through formal education before mini C-arm use. Questions/purposes We questioned whether a radiation safety educational program de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…These results are consistent with the results of a study involving orthopaedic residents who used a mini C-arm and were exposed to radiation for significantly shorter periods following participation in a radiation safety training programme lasting 3 hours (Gendelberg, Hennrikus, Slough, Armstrong, & King, 2016). The results are also consistent with a study conducted by Sheyn et al (2008), which examined the effects of radiation safety education in doctors and employees of a paediatric interventional radiology suite and showed that doctors' use of leaded eyeglasses and hanging shields increased significantly following receipt of the education.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with the results of a study involving orthopaedic residents who used a mini C-arm and were exposed to radiation for significantly shorter periods following participation in a radiation safety training programme lasting 3 hours (Gendelberg, Hennrikus, Slough, Armstrong, & King, 2016). The results are also consistent with a study conducted by Sheyn et al (2008), which examined the effects of radiation safety education in doctors and employees of a paediatric interventional radiology suite and showed that doctors' use of leaded eyeglasses and hanging shields increased significantly following receipt of the education.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with the results of a study involving orthopaedic residents who used a mini C‐arm and were exposed to radiation for significantly shorter periods following participation in a radiation safety training programme lasting 3 hours (Gendelberg, Hennrikus, Slough, Armstrong, & King, ). The results are also consistent with a study conducted by Sheyn et al.…”
Section: Discussionsupporting
confidence: 87%
“…[9][10][11][16][17][18][19][20] A previous study found that an educational program on radiation safety significantly decreased both radiation time and amount in the short term. 12 For residents at the end of the second academic year who had undergone mini C-arm training at the beginning of the year, there was a statistically significant decrease in reduction time for distal radius fractures. Although no significant decrease was found for both bone forearm fracture reduction times, a reduction was noted in radiation emitted with these fracture types.…”
Section: Discussionmentioning
confidence: 91%
“…Sumko et al 11 showed the importance of technique and experience for radiation safety; more junior residents received greater radiation exposure than more experienced residents. Further, Gendelberg et al 12 showed that an educational program on radiation safety decreased radiation time and radiation exposure among residents in the short term. However, it is unclear whether these effects are maintained.…”
Section: Decreased Radiation Exposure Among Orthopedic Residents Is Mmentioning
confidence: 99%
See 1 more Smart Citation